Sosialisasi Pemanfaatan Limbah Tahu Sebagai Proteksi Korosi - Mulyaningsih, Nani; Rahayu, Yunita; Salim, Muhammad Faiz; Taufik, Ikhwan; Salahudin, Xander (Universitas Nusantara PGRI Kediri, 2025)
Liquid waste from the tofu industry can lead to environmental pollution if not properly managed. However, this waste holds potential for innovative use, such as being repurposed as a corrosion control material. This Community Service activity aimed to educate tofu producers in Magelang Regency on processing tofu waste into materials for metal corrosion protection. The approach involved counseling sessions and practical demonstrations. The results showed that tofu waste could reduce corrosion on metal equipment by 40% compared to untreated equipment. The participants showed great enthusiasm, as the method proved practical and easy to apply. In conclusion, this activity significantly contributed to better tofu waste management, helping to minimize environmental pollution risks.